(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
This Study Deals With The Subject Of Management Of The Different Organizations Under The Use Of The Techniques Of The Information And Communication Technology, That Has Become Of The Use Of This Techniques In The Organizations That Manage More Than Necessary Because They Offer Competitive Advantages In A Very Competitive Organizational Environment, It Has Become A Question Of Inevitability Of Use In The Administrative Process Imposed By The Logic Of The Information Society And The Digital Revolution, Where To Take This Concept A Different Approach In Organizations Today Compared To What Organizations Were In The Past, Where Now The Importance Of Application Of Technology Management In Organizations, By Ensuring The Provision Of Appropriate Information Networks And Good Management , As Well As Protecting It From Penetration Operations To Ensure The Confidentiality Of Informations And Data And Work To Maintain Constant, To Ensure The Organizations Its Continuity. Keywords - ICT Technologies, Contemporary Organizations, IT Networks, Electronic Documentation, The Administrative Process.